2015
DOI: 10.1111/jerd.12122
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Surgical Flap for Root Coverage in Association with Grafting Materials

Abstract: Graft survival plays a decisive role in mucogingival therapy results and the selection of the appropriate surgical technique is important to achieve it. This 12-month randomized study showed that an extended flap is able to improve the results of root coverage of localized gingival recessions not only when using the acellular dermal matrix as shown in a previous study, but also when using the subepithelial connective tissue. On this basis, this surgical technique can be suggested as the procedure of choice for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…Forty‐eight studies (reported in 57 papers) were included in the review, with 20 providing data for meta‐analyses. Nine RCTs had their data reported in two articles each (i.e., according to the follow‐up period or type of data (i.e., clinical or patient‐reported outcomes) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty‐eight studies (reported in 57 papers) were included in the review, with 20 providing data for meta‐analyses. Nine RCTs had their data reported in two articles each (i.e., according to the follow‐up period or type of data (i.e., clinical or patient‐reported outcomes) .…”
Section: Resultsmentioning
confidence: 99%
“…ACC, GR change, CAL change and KTW change: ACC related to patient's opinion was reported in 10 RCTs (Table ) Given the heterogeneity of methods/criteria used to assess this outcome and types of procedures compared, formal pooling of data via meta‐analysis was precluded. Of the 48 included trials, 18 evaluating single GR and two multiple GR were included into 11 sets of meta‐analyses (Table ). In addition, data from studies not included in meta‐analyses are presented in supplementary Appendix in online Journal of Periodontology .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, for ADM, complete coverage by the flap is required to achieve optimal vascularization, while for SCTG, the site can be left partially covered [9,20]. A flap thickness of more than 0.8 mm and the suturing of the gingival margin at 2.5 mm coronal to the CEJ will increase root-coverage potential.…”
Section: Discussionmentioning
confidence: 99%
“…Where SCTG is concerned, preexisting blood vessels anastomose with those in the gingival corium with ADM. However, cells and blood vessels from the recipient site are relied on completely to facilitate incorporation [20].…”
Section: Discussionmentioning
confidence: 99%